Pemberdayaan Calon Guru Sekolah Dasar dalam Keterampilan Berpikir Tingkat Tinggi Melalui MOOC-Science - Utama, Candra; Susilo, Herawati (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
The demands of the National Standards for Higher Education require undergraduate graduates to be able to think at a high level. In addition, the demands of the disruption era want technology-based education and learning. The COVID-19 pandemic has become a momentum to integrate the two because learning is forced to be done at home with online learning. The results of the preliminary study show that students in online learning are not able to proactively compile their knowledge and lecturers need curriculum tools that refer to high-level thinking according to government demands. Based on the two demands and the results of the preliminary study, a solution is needed. One of the preferred solutions is curriculum development through MOOC-Science development research efforts to improve the high-level thinking skills of prospective elementary school teachers. This research aims to develop MOOC-Science that has valid multimedia content that can improve high-level thinking skills and analyze the effectiveness of MOOC-Science on higher-level thinking skills. This development research uses a 4D model research design consisting of 1) definition; 2) planning; 3) development; and 4) the spread. The data analysis used is descriptive analysis and statistical analysis. The results of the study concluded that 1) multimedia MOOC-Science is very well validated; 2) the high-level thinking skills instrument is very well validated; and 3) MOOC-Science has proven to be very effective in improving the higher-level thinking skills of prospective elementary school teachers. Suggestions for other researchers can use MOOC-Science with the addition of more complex multimedia features as an alternative to improving the higher-level thinking skills of prospective elementary school teachers.